2019
DOI: 10.15581/018.op-326
|View full text |Cite
|
Sign up to set email alerts
|

Tres claves para afrontar la transformación digital: organización, desempeño y gestión de datos

Abstract: Palabras clave: transformación digital; nuevas tecnologías; gestión de personas / agile; HR Analytics; inteligencia artificial; evaluación del rendimiento; millennials; generación Z; humanismo digital; cambios organizativos; gestión del cambio. OP-326 Tres claves para afrontar la transformación digital: organización, desempeño y gestión de datos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…After the first-round, the participants suggested factors that are associated with digital learning to empower and help businesses overcome the challenges that arise with digital transformation. This dimension was added in the second-round and was evaluated as an important dimension for achieving a digital culture (Media = 4.0), in accordance with the literature (Ochoa, 2016;Villaplana and Stein, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the first-round, the participants suggested factors that are associated with digital learning to empower and help businesses overcome the challenges that arise with digital transformation. This dimension was added in the second-round and was evaluated as an important dimension for achieving a digital culture (Media = 4.0), in accordance with the literature (Ochoa, 2016;Villaplana and Stein, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…McKinsey & Company found that 80% of the companies surveyed started with a digital transformation. Still, only 14% reported an improvement in their performance, while only 3% indicated that the change had succeeded, confirming the challenge of digital transformation (Villaplana and Stein, 2019). Some of the most common organizational barriers to digital transformation are unclear vision and goal of digital transformation; lack of management understanding, knowledge, and experience; lack of leadership skills; lack of organizational agility; rewards and incentives that are not aligned with digital transformation; unclear measurement and reward system; lack of employee engagement; and employee resistance to change (Mirković et al, 2019).…”
Section: Theorymentioning
confidence: 98%
See 1 more Smart Citation